What Determines Host Range and Reproductive Performance of an Invasive Ambrosia Beetle Euwallacea fornicatus; Lessons From Israel and California - Mendel, Zvi; Lynch, Shannon C.; Eskalen, Akif; Protasov, Alex; Maymon, Marcel; Freeman, Stanley (Frontiers in Forests and Global Change, 2021)
This study examined the polyphagous shot hole borer (PSHB) Euwallacea fornicatus (Coleoptera; Scolytinae) native to Southeast Asia and concentrated on its wide host range in two of the invaded areas, California and Israel. Among the 583 examined tree species, 55.9% were characterized as 'non-reproductive hosts' and only 13.8% were characterized as 'reproductive hosts', suitable for the E. fornicatus reproduction. Families that included ≥ 20 species and genera with ≥ 10 were considered for further analysis. The highest percentage of tree species suitable for reproduction was obtained for Salicaceae and Sapindaceae , whereas the lowest percentage of tree species belonging to this category were within the Rosaceae, Myrtaceae and Magnoliaceae. The genera Acer, Quercus and Acacia displayed the highest percentage within the 'reproductive host' category, with the former significantly higher from all seven of the studied genera. We found that all Brachychiton and Erythrina were attacked and none of the examined 20 Eucalyptus spp. were suitable for E. fornicatus reproduction. The results suggest discordance between host tree phylogeny and susceptibility to the E. fornicatus, indicating that trait correlation of susceptibility of different tree species to the E. fornicatus are the results of convergent evolution and not of a common descent. A theoretical model, suggesting the different possibilities of potential tree species becoming attractive or non-attractive to E. fornicatus attack, is described. It is suggested that the beetle reproduction success rate over a wide host range, as well as the long list of species belonging to the 'non-reproductive host' category, is the outcome of interactions between the beetle fungal symbiont, F. euwallaceae, and sapwood of the attacked tree. The model suggests that a tree selected by the E. fornicatus may fall in one of three groups, (i) those in which F. euwallaceae is unable to develop, (ii) those tree species that slow the development of the fungus, and (iii) those that enable F. euwallaceae to thrive. Hence, the host range suitable for beetle reproduction is determined by development of F. euwallaceae. In general, PSHB does not distinguish between host species of the 'non-reproductive host' and 'reproductive host' categories.